1971
DOI: 10.1063/1.1693497
|View full text |Cite
|
Sign up to set email alerts
|

High Temperature Viscosity Ratios for Neon

Abstract: Capillary flow viscometry measurements were made to determine neon viscosity ratios . η(T)/η(T0). T ranges from 1100 to 2100 °K and T0 is the reference, arbitrarily taken as 283 °K. Results are higher than those of previous workers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
6
0

Year Published

1978
1978
2008
2008

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 3 publications
2
6
0
Order By: Relevance
“…( 4) (the solid lines in the figure) agree well with new, adequately reliable test results throughout the investigated temperature range [5,7,[10][11][12][13][16][17][18][19]. A similar picture is seen for the other monatomlc gases [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23]. Thus, Eq.…”
Section: (4)supporting
confidence: 82%
“…( 4) (the solid lines in the figure) agree well with new, adequately reliable test results throughout the investigated temperature range [5,7,[10][11][12][13][16][17][18][19]. A similar picture is seen for the other monatomlc gases [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23]. Thus, Eq.…”
Section: (4)supporting
confidence: 82%
“…Slaman [7]; -· -· -· potential by Cybulski and Toczylowski [6]; ----potential by Wüest and Merkt [5]. Stensland [40]; Vogel [29], fitted values; Vogel [29], experimental data corrected according to new helium standard. Calculated values:…”
Section: Discussionmentioning
confidence: 99%
“…This demonstrates that the measurements by Vogel with his all-quartz oscillating-disc viscometer represent the best experiments in this temperature range. The comparison concerning the experimental data by Dawe and Smith [39] and by Guevara and Stensland [40], which result from relative measurements with capillary viscometers based on a reasonable calibration at room temperature, shows that these data should be influenced by systematic errors. Lastly it is concluded that the theoretical determination of viscosity values is to be preferred to experiments at these high temperatures.…”
Section: Viscositymentioning
confidence: 99%
“…Deviations of experimental and calculated viscosity coefficients from values cal(pres) calculated with the new interatomic potential for Ne at higher temperatures. Experimental data with uncertainties characterized by error bars: 5 Kestin et al [27], best estimate; Hellemans et al [37]; Kestin et al [38]; s Dawe and Smith [39]; oe Guevara and Stensland [40]; i Vogel [29], fitted values; m Vogel [29], experimental data corrected according to new helium standard. Calculated values: Á Á Á Á Á Á Á Á Á fifth-order classical calculation [] cl,5 ; ----potential by Aziz and Slaman [7]; -Á -Á -Á potential by Cybulski and Toczylowski [6]; ----potential by Wu¨est and Merkt [5].…”
Section: Viscositymentioning
confidence: 99%